2016
DOI: 10.18203/2349-2902.isj20164458
|View full text |Cite
|
Sign up to set email alerts
|

Managing bilateral inguinal hernia laparoscopically: is it gold standard?

Abstract: Background:Even after many studies done in recent years, no consensus has been achieved on the surgical technique of inguinal hernia repair. It was believed that in bilateral inguinal hernia cases laparoscopic surgery is very much advantageous as it can be done through same incisions as unilateral laparoscopic inguinal hernia repair (no additional incision required), whereas in open surgery for bilateral case separate groin incision for each side required. Aim of this study is to evaluate and compare results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…These data are in accordance with other authors' reports. 1,2,5,10,12,13 Data concerning postoperative complications and recurrence showed similar results for conventional open and laparoscopic procedures, recent studies publishing close results. [1][2][3]5,8,10,12,13,15 Postoperative pain was significantly lower for patients in the laparoscopic group, similar results being found in other studies.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These data are in accordance with other authors' reports. 1,2,5,10,12,13 Data concerning postoperative complications and recurrence showed similar results for conventional open and laparoscopic procedures, recent studies publishing close results. [1][2][3]5,8,10,12,13,15 Postoperative pain was significantly lower for patients in the laparoscopic group, similar results being found in other studies.…”
Section: Discussionmentioning
confidence: 84%
“…1,2,5,10,12,13 Data concerning postoperative complications and recurrence showed similar results for conventional open and laparoscopic procedures, recent studies publishing close results. [1][2][3]5,8,10,12,13,15 Postoperative pain was significantly lower for patients in the laparoscopic group, similar results being found in other studies. 1-3, 7,10,11,12,14 Also, we observed that patients who underwent laparoscopic surgery returned earlier to work and started physical activity (sports) earlier.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations